MOSQUE WAQF LAND MANAGEMENT (Management Analysis of Waqf Land At-Taqwa Mosque, Soco Village, Slogohimo District, Wonogiri Regency) - Makhda Intan Sanusi Intan (Jurnal Ekonomi, 2022)
In Indonesia, waqf is very closely related to land waqf even though in essence the objects that can be donated cannot be separated from the land. Besides that, the existing waqf data is not accurate considering that data on waqf assets is not well coordinated and arranged in a professional institution. The most important thing about waqf management is the experience of the nazirs in developing waqf. Therefore management occupies the most urgent position in the world of waqf. Because, the most decisive waqf object is more useful or not depending on the pattern of management. This study aims to: (1) To find out critically and in depth the implementation of waqf land management at the At-Taqwa mosque. (2) To critically explore waqf land management practices using a Nazir organization. (3) To obtain a transformative picture of the impact of the use of the Naz}hir organization on the development of waqf land area and its assets. This study uses a qualitative approach. The location of this research is the waqf land of the At-Taqwa mosque, Soco Village, Slogohimo District, Wonogiri Regency. This research data collection was carried out through in-depth interviews and documentation. Data analysis was performed using an inductive descriptive method. Descriptive means explaining in as much detail as possible the management of waqf land at the At-Taqwa mosque, so that real, factual and accurate conclusions can be obtained regarding the facts, characteristics and relationships between the phenomena being financed. So that it can be used to make conclusions with the right interpretation. Inductive, a way or way used to gain scientific knowledge starting from observations on the management of waqf land at the At-Taqwa mosque, in detail, then draws general conclusions. Based on the process of data collection and analysis, this study produced three findings. First, that the management of waqf land at the At-Taqwa mosque, Soco Village, Slogohimo District, Wonogiri Regency has not fulfilled good or professional management because there are several functions and management processes that have not been fulfilled. Second, the nadzir which is used to manage waqf land at the At-Taqwa mosque is a nadzir organization, because the nadzir organization is better able to maintain waqf assets and is better able to enhance the roles of the kenazir's to manage waqf properly. Third, that the use of the Nadzir organization at the At-taqwa mosque has both positive and negative impacts. The positive impact is that waqf land has developed quite well in terms of the area of ​​mosque waqf land and its assets, nadzir can be productive of waqf land. As for the negative impact of productive waqf here, it does not have an important enough contribution in community empowerment.